Autophagy and Exosome Coordinately Enhance Macrophage M1 Polarization and Recruitment in Influenza A Virus Infection - Xia, Chengjie; Xu, Weiming; Ai, Xin; Zhu, Yingqi; Geng, Ping; Niu, Yijun; Zhu, Haiyan; Zhou, Wei; Huang, Hai; Shi, Xunlong (Frontiers in Immunology, 2022)
Influenza A virus infection results in viral pneumonia, often accompanied by the infiltration and recruitment of macrophages, overactivation of inflammatory responses, and obvious cell autophagy and exosome production. However, little is known about the roles of autophagy and exosome in these inflammation responses. In this study, multiple methods were applied to explore the possible influence of autophagy and exosome from these infected host cells, such as flow cytometry, qRT-PCR, immune-fluorescence technology, Western blot. Results: More M1 polarized macrophages (CD11b+/F4/80+/CD86+) were recruited to the lung tissues of infected mice, which could be mimicked by tracking the movement of macrophages to those H1N1-infected cells in vitro (Transwell assays). Besides, there was some coordinate up-regulation of M1 polarization signs (iNOS/Arg-1 bias), and autophagy biomarker (LC3), as well as exosome biomarker (CD63) in the infected macrophages and epithelial cells. Furthermore, exosomes extracted from virus infected cells’ supernatant were proved to promote more peritoneal macrophages recruitment and polarization than the normal group. The fluorescence co-localization of LC3-CD63 and inhibition of autophagy and exosome signal pathway further revealed that H1N1 infection seemed to sequentially activate the macrophage M1 polarization and recruitment via an autophagy-exosome dependent pathway. Conclusion: Autophagy and exosome coordinately enhanced the macrophage M1 polarization and recruitment in influenza virus infection, which also provides potential therapeutic targets for influenza virus infection.